Philosophy of quantum mechanics: quantum holism to cosmic holism: the physics and metaphysics of bohm - Chandrankunnel, Mathew (Global Vision Publ. House, 2008)
section 1. Bohm, physicist philosopher of holism -- section 2. The foundational problems in quantum mechanics -- section 3. Quantum holism : Bohmian mechanics -- section 4. Cosmic holism : Bohmian metaphysics